ATTAC! Development of a Novel Advanced Trauma Team Application Course. Issue 2 (March 2023) - Orr, Lanny; Stevens, Lisa; McCotter, Elizabeth; Peterson, Alexa; Brant, Jeannine M.; Thompson, Simon J.
Abstract : BACKGROUND: Although existing trauma nurse courses provide basic education, advanced courses with simulation experiences that enhance team leadership, communication, and workflows are lacking. OBJECTIVE: To design and implement the Advanced Trauma Team Application Course (ATTAC) to promote advanced skills for nurses and respiratory therapists with varied experience and skill levels. METHODS: Trauma nurses and respiratory therapists were selected to participate based on years of experience and the novice to expert nurse model. Two nurses from each level (excluding novice) participated, ensuring a diverse cohort to promote development and mentorship. The 11-module course was presented over 12 months. A five-question survey was employed at the end of each module to self-evaluate assessment skills, communication skills, and comfort for trauma patient care. Participants rated skills and comfort on a "0–10" scale, with 0 being "not at all" to 10 being "extensively." RESULTS: The pilot course was conducted from May 2019 to May 2020 at a Level II trauma center in the Northwest United States. Nurses reported ATTAC improved assessment skills, team communication, and comfort in caring for trauma patients (mean = 9.4; 95% CI [9.0, 9.8]; scale of 0–10). Participants indicated scenarios closely mimicked real-world situations; concept application commenced directly following each session. CONCLUSION: This novel approach to advanced trauma education promotes development of advanced skills that enable nurses to anticipate needs rather than being reactive, engage in critical thinking, and adapt to rapidly changing patient conditions.